Conceptual framework of women’s food environments and determinants of food acquisition and dietary intakes in low- and middle-income countries: a scoping review - O’Meara, L.; Bruyn, J. de; Hope, T.; Fajó-Pascual, M.; Hodge, R.; Turner, C.; Stoynova, M.; Wellard, K.; Ferguson, E.; Dominguez-Salas, P. (Elsevier, 2025)
Women in low-income and middle-income countries (LMICs) are disproportionately affected by malnutrition in all its forms. Diets link human health and environmental sustainability; however, existing food environment frameworks rarely consider the unique needs of women that can differ due to sociocultural norms and lower social status, potentially reducing the effectiveness of nutrition initiatives. We conducted a systematic scoping review of peer-reviewed literature published in English, Spanish, Portuguese, and French to identify determinants of food acquisition and dietary intake of women in LMICs. By synthesising evidence from 518 studies across 125 countries, we identified 143 eco-social, structural, and individual-level determinants to develop an empirically grounded food environment conceptual framework for women. Women’s agency—encompassing decision making and financial autonomy, bargaining power, control over time, and freedom of movement—emerged as a prominent mediator of food acquisition practices and dietary intakes across diverse regions and the rural–urban continuum. Our findings highlight the importance of addressing legislative, structural, and sociocultural determinants mediating women’s agency, alongside other key external and individual-level food environment determinants influencing procurement and consumption of nutritious diets. This empirically grounded conceptual framework can guide research priorities and analytical approaches and identify intervention points for policies and programmes to optimise women’s nutrition.